1999
DOI: 10.1159/000016506
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Counts in Carious Dentine under Restorations: 2–Year in vivo Effects

Abstract: Little is known about the long–term effects of fluoride–releasing materials on carious dentine in vivo. The aim was to investigate the 2–year influence of a resin–modified glass ionomer cement (RM–GIC) and amalgam on the bacteriological counts of carious dentine that remained under class I restorations. To enable a split–mouth design, 33 molar pairs in 33 patients (mean age 15.1 years, SD 1.4) were selected, based on clinically and radiographically diagnosed occlusal dentine caries. The enamel of the carious m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 7 publications
1
70
1
3
Order By: Relevance
“…Since cavity preparation usually involves some loss of healthy dental tissue, alternative approaches have been proposed to preserve tooth structure, such as the sealing of carious tissue beneath sealants or restorations. These approaches may even reduce or completely eliminate the population of viable microorganisms, 1,2,3,4,5,6,7,8 thus controlling caries progression.…”
Section: Introductionmentioning
confidence: 99%
“…Since cavity preparation usually involves some loss of healthy dental tissue, alternative approaches have been proposed to preserve tooth structure, such as the sealing of carious tissue beneath sealants or restorations. These approaches may even reduce or completely eliminate the population of viable microorganisms, 1,2,3,4,5,6,7,8 thus controlling caries progression.…”
Section: Introductionmentioning
confidence: 99%
“…2 At the same time, removal of carious dentin is necessary prior to restoring the tooth. 3 Although there still is no definitive guideline as to how much infected dentin may be allowed to remain in the cavity, it is generally accepted that heavily infected dentin needs to be removed and minimal quantities of bacteria may be left in the cavity in order to preserve dentin. [4][5] A clinically relevant method for assessing new caries excavation methods should both quantify the infected dentin remaining in the cavity after excavation and assess the amount of dentin that has been removed.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques show success in clinical studies and microbiological reports examining bacterial presence after such procedures have demonstrated that the number of microorganisms is reduced after incomplete carious dentin removal and tooth sealing [5][6][7][8][9]. However, the persistence of viable bacteria in dentin after these techniques has raised doubts regarding the long-term effectiveness of treatment [31]. Streptococcus mutans are cariogenic bacteria that may be found on sealed carious dentin [2,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%